International Trends in Adolescent Screen-Time Behaviors From 2002 to 2010 - Bucksch, Jens; Sigmundova, Dagmar; Hamrik, Zdenek; Troped, Philip Jay; Melkevik, Ole; Ahluwalia, Namam; Borraccino, Alberto; Tynjälä, Jorma; Kalman, Michal; Inchley, Joanna (Journal of adolescent health, 2016)
PURPOSE: Engaging in prolonged screen-time behaviors (STBs) is detrimental for health. The objective of the present analyses was to examine temporal trends in TV viewing and computer use among adolescents across 30 countries. METHODS: Data were derived from the cross-national Health Behaviour in School-aged Children study. Data on TV viewing and computer use for gaming and nongaming purposes were collected in 2002 (n = 139,725 [51.4% girls]), 2006 (n = 149,251 [51.3% girls]), and 2010 (n = 154,845 [51.2% girls]). The temporal trends in TV viewing and computer use were each tested for all countries combined and for each individual country by sex-specific univariate analysis of variance. RESULTS: Between 2002 and 2010, TV viewing decreased slightly in most of the 30 countries among both boys and girls. This decrease was more than offset by a sharp increase in computer use, which was consistent across all countries. Overall, boys reported more hours of STBs. They also reported a slightly larger decrease in TV viewing and slightly larger increase in computer use. STBs were generally more frequent on weekend days. CONCLUSIONS: The overall cross-national increases in STBs should be a call to action for public health practitioners, policy-makers, and researchers that interventions specifically focused on reducing STBs in youth are sorely needed. Because all countries experienced a trend in the same direction, it might be fruitful to learn more about the determinants of STBs among those countries in which hours of STBs are generally low as compared with other countries.
Keywords: zdravotnické přehledy; Sedentary Behavior; Female; Television; ženské pohlaví; sedavý životní styl; průřezové studie; Adolescent Behavior; Adolescent; Global Health; celosvětové zdraví; lidé; Computers; Sex Factors; Cross-Sectional Studies; Male; sexuální faktory; televize; mladiství; počítače; Health Surveys; mužské pohlaví; chování mladistvých; Humans